PENGARUH KOMPENSASI DIREKSI DAN EMPLOYEE STOCK OWNERSHIP PROGRAM (ESOP) TERHADAP KINERJA PERUSAHAAN (Studi pada Consumer Goods Go Public yang Terdaftar di Bursa Efek Indonesia) Periode 2013 – 2017 - Septiana Sisca Mariana Talohanas; Sparta (Journal of Accounting, Management and Islamic Economics, 2025)
Company performance is one measure of company success that is the result of all activities and activities of the company. Good company performance is reflected in its financial statements. So that the main users of the company's financial statements such as company management and investors can use this information to make the right decisions and policies. This study began from 2013 to 2017. The method used in this study is Multiple Regression Analysis, T Test with a significance level of 5% and processed using EViews 9.1. The results of this study indicate that partially the Compensation of Directors and ESOP does not have a significant positive effect on company performance. Meanwhile Company Size and Leverage have a significant influence on company Performance. The results of this study have implications for management, supervision, and academics namely the need to consider Directors' Compensation, ESOP, Company Size and Leverage.